Efforts To Increase Personal Hygiene Through Personal Hygiene Motivation On Patient - Yudhana, Syela Ambri, Arif Widodo, A.Kep.,M.Kes (2017)
Background: The lack of self-care is a condition where the person is unable to perfom self-care independently, clients wih metal illness will experience the lack of self care so it causing problems with self-care deficit, from nursing problems in RSJD Arif Zainudin Surakarta often found clients with deficit disorser treatment as many 1,250 clients themselves Objective: To understand the nursing care in patients with a diagnosis of self-care deficit in Sena RSJD Arif Zainudin Surakarta Methods: The method that used is descriptive studies, data collection techniquese with interviews, observations, and perfom nursing care as issue of self-care deficit Results: After 3x24 hour nursing care for patients with self-care deficit the problems with personal hygiene, dressing, eat and drink, defecate or urinate issues are resolved and the intervention is stopped Conclusion: Motivation can encourage clients to perfoms activities independently, cooperation between the health care team and family are indispensable for the succed of nursing care to clients with self-care deficit